A Small Structural Monetary Policy Model for Small Open Economies with Debt Accumulation - Karam, Philippe (IMF Working Papers; Working Paper, 2008)
We extend a small New Keynesian structural model used for monetary policy analysis to address a richer class of policy issues that arise in open economy analysis. We draw a distinction between absorption and domestic output, and as the difference between the two is effectively the current account, there is now an explicit accumulation or decumulation of foreign liabilities in response to various shocks affecting the system. Such stock equilibria can now have an impact back on to the flows in the domestic economy. We perform simulations using parameters calibrated to the Canadian economy and compare the differences in impulse responses from the original model. Advantages in a forecasting environment owing to the ability to impose explicit projections about imports and exports are also exposed.